Oxidation of aminoalkyl and hydroxylaminoalkyl furans. Issue 50 (16th December 2015) - Kazancioglu, Mustafa Zahrittin; Akin Kazancioglu, Elif; Secen, Hasan; Altundas, Ramazan
Graphical abstract: Abstract: The oxidation reactions of amino and hydroxylamino substituted alkylfurans were explored for the synthesis of structurally complex compounds from simple starting materials. A novel photooxygenation of the furan derivatives gave an α, β-unsaturated dicarbonyl moiety which underwent subsequent conjugate addition to yield diastereomeric mixtures of the corresponding pyrrolidine and isoxazoline heterocycles. Oxidation of the α, β-unsaturated dicarbonyl using m CPBA gave epoxide intermediates, which were opened by nucleophilic attack of the amino groups, furnishing pyrrolidine and isoxazolidine heterocycles.